2010
DOI: 10.1063/1.3300836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on interstitial-related luminescence centers in silicon

Abstract: Impact of oxygen on the permanent deactivation of boron-oxygen-related recombination centers in crystalline silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
(27 reference statements)
3
18
0
Order By: Relevance
“…Photoluminescence measurements indicate that the W line intensity is maximized after annealing in the range 250 − 300 • C and vanishes upon annealing at ∼ 500 • C [5,6]. As the W line intensity diminishes in PL spectra, the X line raises and reaches maximum intensity after annealing in the range 400−500 • C and vanishes upon annealing at ∼ 600 • C [5,6,8].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Photoluminescence measurements indicate that the W line intensity is maximized after annealing in the range 250 − 300 • C and vanishes upon annealing at ∼ 500 • C [5,6]. As the W line intensity diminishes in PL spectra, the X line raises and reaches maximum intensity after annealing in the range 400−500 • C and vanishes upon annealing at ∼ 600 • C [5,6,8].…”
Section: Introductionmentioning
confidence: 98%
“…As the W line intensity diminishes in PL spectra, the X line raises and reaches maximum intensity after annealing in the range 400−500 • C and vanishes upon annealing at ∼ 600 • C [5,6,8]. The temperature regime at which their presence is maximized along with the fact that their intensity decreases as the damage concentration increases suggest that defects responsible for these lines should be of small size [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the luminescence from the W-center is seen to reach a maximum after a 225-275ºC annealing and can be reduced to levels where they are no longer observed after annealing at temperatures around 450ºC [4][5]. Although different experiments have shown that these lines are related to small defects generated by ion implantation [2][3][4][5][6], it is not quite clear yet which is the specific defect that produces them. Some experiments have revealed that they are associated to Si self-interstitial clusters with a small number of Si interstitials [4,6].…”
Section: Interstitial Related Luminescence Centersmentioning
confidence: 89%